Developing the knowledge of one’s own labor activity as a factor of an employee’s economic security - L. A. Bogunov (Russian Journal of Economics and Law)
Objective: to disclosure of conceptual aspects of the competence of managing an employee’s economic security from the viewpoint of developing one’s knowledge of labor activity.Methods: to achieve the goal and solve the set tasks, we used elements of dialectical, system, competence approaches and, accordingly, methods of system analysis and synthesis, the method of formalization, and the principle of development. Results: under digitalization of economic processes, the increased role of competencies and skills of personnel, the problem of threat to economic security of employees is aggravated. At the same time, human capital becomes the leading resource in the knowledge economy. Based on the analysis of the theoretical provisions of labor theory, as well as aspects of the theory of human capital and knowledge management, the concept of knowledge of the employee's own labor activity (KEOLA) is formulated. In the context of the existing trends of understanding the phenomenon of economic security and the theory of marginal utility, as well as the proposed KEOLA concept, the notion of economic security of an employee is formulated. It is determined that KEOLA develops in the process of labor activity of an individual, and the vector of development depends on the conditions of labor experience acquisition. A modern employee must learn to manage the utility of one’s own knowledge, which is understood as KEOLA moving from the state of quasi-formalized to para-formalized knowledge in the aspect of determining its general and ultimate utility. It is established that the ability to control the knowledge utility increases through knowledge formalization. Scientific novelty: for the first time, the article reveals the conceptual aspects of the competence management of economic security of an employee from the viewpoint of KEOLA development in the aspect of general and marginal utility of one’s knowledge, which is especially important in the context of current trends of economy digitalization and employment robotization. Practical significance: the main provisions and conclusions of the article can be used, first, for the further theoretical development of substantive aspects of competence of economic security management of an employee, and second, as targets in the training of modern specialists as competent employment actors under knowledge economy.